2011
DOI: 10.2460/ajvr.72.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cytokine-induced prostaglandin E2 production in cultures of articular chondrocytes obtained from carpal joints of camels (Camelus dromedarius)

Abstract: Chondrocytes proliferated without loss of the cartilage phenotype. Responses to cytokines were significantly inhibited by the mixtures of ASU + GLU + CS and PPS + NG, which indicated that this response can be modulated. This culture technique can be used to study the functional properties of camel chondrocytes and identify agents that may potentially be used to treat and manage joint inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…ASU and EGCG have both been documented for their anti-inflammatory activity [7,8,11,12]. Of the two compounds, ASU has been reported to have pro-anabolic activity and has been used for OA management in both humans and animals [6,24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ASU and EGCG have both been documented for their anti-inflammatory activity [7,8,11,12]. Of the two compounds, ASU has been reported to have pro-anabolic activity and has been used for OA management in both humans and animals [6,24].…”
Section: Resultsmentioning
confidence: 99%
“…Following pre-treatment, cultures were incubated with control media alone or activated with human recombinant cytokines IL-1β (10 ng/mL; R&D Systems, Minneapolis, MN) and TNF-α (1 ng/mL; Sigma-Aldrich) for 1 h to measure gene expression by real-time PCR, NF-κB immunohistochemistry, or Western blot. Earlier studies have confirmed the combination of IL-1β + TNF-α at these concentrations to be a potent activator for chondrocytes from several different species including equine and camel [8,16]. Following activation, supernatant was removed and a set of 6-well plates was stored at -80°C for gene expression analysis while another set was used for nuclear fractionation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ASU, GLU and CS have been documented to reduce inflammation in vitro [9] [10] [11], [31]- [38], and in vivo [39]- [46]. These agents have been reported to ameliorate OA in man and animals with minimal adverse side effects [39]- [46].…”
Section: Introductionmentioning
confidence: 99%